Рульовий механізм транспортного засобу з вмонтованим підсилювачем - Підгаєцький, М. М.; Повєткін, С. М.; Біляковський, Р. П.; Pidhaietskyi, M.; Povietkin, S.; Biliakovskyi, R.; Пидгаецкий, М. М.; Поветкин, С. М.; Биляковский, Р. П. (Український інститут промислової власності, 2004)
Винахід відноситься до транспортного машинобудування зокрема до рульових механізмів з вмонтованим гідравлічним підсилювачем. Steering gear of a vehicle with a mounted amplifier contains housing, in which the piston is mounted, one part of which has axial opening and divides the interior of housing into two working chambers connected through the distributor with the source of pressure of fluid.
Steering gear with built-in amplifier